2013
DOI: 10.3109/10428194.2013.783909
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab, cyclophosphamide-fractionated, vincristine, doxorubicin and dexamethasone alternating with rituximab, methotrexate and cytarabine overcomes risk features associated with inferior outcomes in treatment of newly diagnosed, high-risk diffuse large B-cell lymphoma

Abstract: Subtypes of diffuse large B-cell lymphoma (DLBCL) that have inferior outcomes after front-line therapy with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone) have been identified. While it is agreed that R-CHOP is probably not adequate in these patients, there is no standard treatment approach for patients with DLBCL with high-risk features. We present results of a retrospective cohort study of high-risk DLBCL (defined as having at least one unfavorable risk factor: non-germinal cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The primary intention of the study was to determine whether initial intensive chemotherapy with R-HCVAD/R-MA, compared with standard R-CHOP, could overcome the adverse biology and improve outcome in patients with high-risk DLBCL. The retrospective analyses on which our trial was based revealed promising efficacy data (Fayad et al, 2007) , (Mato et al, 2013). To prospectively compare the safety and efficacy of R-HCVAD/R-MA with R-CHOP, a randomized trial was considered necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The primary intention of the study was to determine whether initial intensive chemotherapy with R-HCVAD/R-MA, compared with standard R-CHOP, could overcome the adverse biology and improve outcome in patients with high-risk DLBCL. The retrospective analyses on which our trial was based revealed promising efficacy data (Fayad et al, 2007) , (Mato et al, 2013). To prospectively compare the safety and efficacy of R-HCVAD/R-MA with R-CHOP, a randomized trial was considered necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Inferior rates of survival have been reported in diffuse large B cell lymphoma (DLBCL) patients harbouring MYC rearrangements compared to those without MYC rearrangements when treated with R‐CHOP (Savage et al , ) and (Barrans et al , ), and recent publications have suggested that the use of higher‐dose first‐line immunochemotherapy may result in improved outcomes in patients with MYC rearrangements (Mato et al , ; Oki et al , ). Accordingly, there is a strong rationale for offering intensive first‐line therapies to patients with MYC‐ rearranged DLBCL (including DH), and the use of dose‐adjusted EPOCH‐R (etoposide, predisone, vincristine, cyclophosphamide, doxorubicin, rituximab; NCT01092182) is currently being evaluated in a multi‐centre phase 2 clinical trial.…”
mentioning
confidence: 99%
“…When we applied the inclusion criteria of each respective trial on our R‐Hyper‐CVAD cohort and investigated outcomes, we found very similar outcome in our patients compared with these three trials, although it seems that treatment‐related mortality in our older patients was lower, which we believe might be due to the flexibility outside trials to switch between regimens, and partly because our patients were treated at a single‐centre with long experience with the regimen. This probably also explains the differences with multi‐centre [ 26 ] and the similarities with single‐centre [ 27 ] studies of R‐Hyper‐CVAD/R‐MA. Still, R‐Hyper‐CVAD/R‐MA causes considerable toxicity, and there were six toxic deaths during induction therapy among the 150 patients who received at least one cycle of R‐Hyper‐CVAD/R‐MA, all in patients aged 54–65.…”
Section: Discussionmentioning
confidence: 99%